The PPARγ agonist, rosiglitazone, attenuates airway inflammation and remodeling via heme oxygenase-1 in murine model of asthma - XU Jing; ZHU Yan-ting; WANG Gui-zuo; HAN Dong; WU Yuan-yuan; ZHANG De-xin; LIU Yun; ZHANG Yong-hong; XIE Xin-ming; LI Shao-jun; LU Jia-mei; LIU Lu; et al. (Acta Pharmacologica Sinica, 2017)
Aim: Rosiglitazone is one of the specific PPARγ agonists showing potential therapeutic effects in asthma. Though PPARγ activation was considered protective in inhibiting airway inflammation and remodeling in asthma, the specific mechanisms are still unclear. This study was aimed to investigate whether heme oxygenase-1 (HO-1) related pathways were involved in rosiglitazone-activated PPARγ signaling in asthma treatment. Methods: Asthma was induced in mice by multiple exposures to ovalbumin (OVA) in 8 weeks. Prior to every OVA challenge, the mice received rosiglitazone (5 mg/kg, po). After the mice were sacrificed, the bronchoalveolar lavage fluid (BALF), blood samples and lungs were collected for analyses. The activities of HO-1, MMP-2 and MMP-9 in airway tissue were assessed, and the expression of PPARγ, HO-1 and p21 proteins was also examined. Results: Rosiglitazone administration significantly attenuated airway inflammation and remodeling in mice with OVA-induced asthma, which were evidenced by decreased counts of total cells, eosinophils and neutrophils, and decreased levels of IL-5 and IL-13 in BALF, and by decreased airway smooth muscle layer thickness and reduced airway collagen deposition. Furthermore, rosiglitazone administration significantly increased PPARγ, HO-1 and p21 expression and HO-1 activity, decreased MMP-2 and MMP-9 activities in airway tissue. All the therapeutic effects of rosiglitazone were significantly impaired by co-administration of the HO-1 inhibitor ZnPP. Conclusion: Rosiglitazone effectively attenuates airway inflammation and remodeling in OVA- induced asthma of mice by activating PPARγ/HO-1 signaling pathway.